Trends in PGMI Students’ Thesis Research: A Comparative Study of Islamic Higher Education in Central Java - Muchamad Fauyan; Hafizah Ghany Hayudinna (Al-Mudarris, 2025)
This study explores the trends in final thesis research among PGMI (Islamic Elementary School Teacher Education) students at UIN K.H. Abdurrahman Wahid Pekalongan and UIN Prof. K.H. Saifuddin Zuhri Purwokerto during the period of 2017-2021. The primary aim is to analyze the chosen research approaches, focuses, and fields of study. The research employed a descriptive analysis method, utilizing data from both universities. The findings indicate that qualitative approaches dominate students’ thesis research. Most studies focus on students, although many are not directly aligned with the academic fields of madrasah ibtidaiyah. When connected to these fields, common research topics include Islamic studies, mathematics, science, thematic learning, local content, extracurricular activities, Bahasa Indonesia, social studies, and civic education. The study recommends enhancing students' understanding of diverse research approaches, encouraging exploration of relevant topics in madrasah ibtidaiyah studies, and fostering stronger integration of research with scholarly fields to contribute more meaningfully to elementary education development.